Dopamine D1 receptors involved in locomotor activity and accumbens neural responses to prediction of reward associated with place - Tran, Anh Hai (National Academy of Sciences, 2005)
Predicting reward is essential in learning approach behaviors. Dopaminergic activity has been implicated in reward, movement, and cognitive processes, all essential elements in learning. The nucleus accumbens (NAc) receives converging inputs from corticolimbic information-processing areas and from mesolimbic dopamine neurons originating in the ventral tegmental area. Previously, we reported that in mice, a dopamine D2 receptor knockout (D2R-KO) eliminated the prereward inhibitory response, increased place-field size of NAc neurons, and reduced locomotor activity without marked change in intracranial self-stimulation (ICSS) behavior. The present study investigated the specific contribution of dopamine D1 receptor (D1R) in mediating reward, locomotor activity, and spatial associative processes and in regulating NAc neural responses. In contrast to D2R-KO animals, here we find D1R-KO in mice selectively eliminated the prereward excitatory response and decreased place-field size of NAc neurons. Furthermore, D1R-KO impaired ICSS behavior, seriously reduced locomotor activity, and retarded acquisition of a place learning task. Thus, the present results suggest that D1R may be an important determinant in brain stimulation reward (ICSS) and participates in coding for a type of reward prediction of NAc neurons and in spatial learning.